Endangered Indigenous Languages of Assam: A Case Study of Deori (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
India is a country, where, in her lap breathe the happy followers of various religions, caste, communities etc. In accordance to language we find many ethnic languages but some of them lack their own script, which may be one of the factors leading to their language extinction. In the north eastern region of India, Assam is the homeland of different ethnic groups. The state has a large number of tribes, each unique in language. Among the different tribes Deori community is one of them who belong to Tibeto-Burmese origin. They have four sub-caste known as Dibongia, Borgoyan, Tengaponia and Patorgoyan. The language is interacting among the Dibongia only but in rare cases the other three sub-caste used it during religious functions and festival. It is because of sheer dearth of written script varied problem are faced by the Deori in both social and political aspect. Deori is presently facing a serious threat of endangerment due to rapid language shift toward dominant languages such as Assamese and English.